Policies and anti communist discourses in Costa Rican postwar, 1948 - 1949 - Barrientos Valverde, Jorge (2017)
We will now see an analysis of policies and anti-communist political representatives who were in state power directly or as collaborators between 1948 and 1949, following the development of the two governments participating in that context speeches. This through official pronouncements in various writings published individually and in print, in addition to official government sources, mainly laws and decrees, reports of ministries and the legislature, presidential speeches, etc. This focus on the logic of the anti-communist argument based on the defense of Western democracy, capitalism, Western customs, and human rights from the state and their governments. In that direction to comparatively examine the anti-communist ideological justifications to analyze their positions, their public policies, repressive actions and decisions according to the different problems presented to them about the communist threat.